2021
DOI: 10.12659/msm.932404
|View full text |Cite
|
Sign up to set email alerts
|

Pseudolaric Acid B Attenuates High Salt Intake-Induced Hypertensive Left Ventricular Remodeling by Modulating Monocyte/Macrophage Phenotypes

Abstract: Background Studies in ApoE knockout mice have shown that pseudolaric acid B (PB) can act as an immunomodulatory drug and attenuate atherosclerosis progression by modulating monocyte/macrophage phenotypes. Our previous study demonstrated that high salt intake could shift the phenotype of monocytes/macrophages to an inflammatory phenotype, and that this shift was related to hypertension and hypertensive left ventricular (LV) remodeling. However, no comprehensive assessment of the effects of PB on hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…This study would have missed changes in neutrophil recruitment, which peaks 1-day post-MI, and would not discriminate between Ly-6C hi and Ly-6C lo monocytes, which peak on day-3 and day-7 post-MI, respectively 30 . Ly-6C hi monocytes are pro-inflammatory whereas Ly-6C lo monocytes have been implicated in resolving the inflammatory response 30,[90][91][92] . In an inflammatory environment such as the infarct zone, monocytes differentiate into macrophages, supplementing the complement of resident macrophages 93,94 .…”
Section: Discussionmentioning
confidence: 99%
“…This study would have missed changes in neutrophil recruitment, which peaks 1-day post-MI, and would not discriminate between Ly-6C hi and Ly-6C lo monocytes, which peak on day-3 and day-7 post-MI, respectively 30 . Ly-6C hi monocytes are pro-inflammatory whereas Ly-6C lo monocytes have been implicated in resolving the inflammatory response 30,[90][91][92] . In an inflammatory environment such as the infarct zone, monocytes differentiate into macrophages, supplementing the complement of resident macrophages 93,94 .…”
Section: Discussionmentioning
confidence: 99%
“…Second, HNP-1 may have a "bipolar effect," such that inflammatory factor expression may be enhanced by a high dose of HNP-1 (100 μg/day) and inhibited by a healthy dose of HNP-1 (5 μg/day or 10 μg/mL) [65]. Third, studies have reported that regulation of the inflammatory response effectively controls BP and ameliorates HLVH [65][66][67][68][69][70][71]. However, NF-κB is a key regulatory signaling pathway in inflammatory immune responses [72][73][74][75], and NF-κB inhibition may ameliorate hypertension and HLVH [76][77][78][79][80][81][82][83][84][85][86].…”
Section: Discussionmentioning
confidence: 99%
“…A long-term high-salt diet can induce hypertension and myocardial hypertrophy. In animal models, mice on a high-salt diet developed left ventricular hypertrophy and reduced cardiac contractile function [ 16 , 17 ].…”
Section: High-salt Dietmentioning
confidence: 99%
“…Yu et al . [ 17 ] intervened in mice for 12 weeks with a diet containing 8% NaCl or a combination of 8% NaCl diet and intraperitoneal injection of N-nitro-L-arginine methyl ester (10 mg/mL, 50 mg/kg/d). In the combined intervention group, the expression of M1 correlation factors such as TNF- , CCL-2, IL-1 , and CCL-5, and M2 correlation factors Ym-1, Arg-1, and IL-10 were significantly increased at the mRNA level.…”
Section: High-salt Dietmentioning
confidence: 99%